Democratic Republic of the Congo : First Review under the Extended Credit Facility Arrangement, Request for Modification of Performance Criteria, and Financing Assurances Review-Press Release; Staff Report; and Statement by the Executive Director for the Democratic Republic of the Congo. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2022)
After a third wave over the summer, COVID-19 cases are declining but vaccination has stalled. Economic activity has improved on the back of strengthened external demand, allowing for a stronger-than-envisaged buildup in international reserves. Inflation and the exchange rate have stabilized. Near-term challenges arise from uncertainty related to the pandemic and the gradual global economic recovery supporting high commodity prices.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Cyprus